The Mediating Role of General Procrastination Behaviors in the Relationship between Self-Control and Social Media Addiction in University Students - SEVİM, ERDEM; EKŞİ, HALİL (TURKISH GREEN CRESCENT SOC, 2019)
The aim of this study is to examine the mediating role of general procrastination behaviors in the relationship between self-control and social media addiction using the structural equation modeling (SEM) technique. It also aims to analyze social media addiction, self-control, and general procrastination behaviors in terms of various demographic variables. The population of the study consists of 5.641 students studying at Marmara Universitys Ataturk Faculty of Education during the 2018 spring semester. The research sample consists of 394 students who have been selected from the population using a multi-stage sampling method. A personal information form, the Social Media Addiction Scale, the General Procrastination Scale, and Brief Self-Control Scale were used in the data gathering process. In order to examine the study, an independent samples t-Test, ANOVA (One-Way Analysis of Variance), Pearson product-moment correlation and path analyses have been used for analyzing the data. The structural equation modeling indicates the mediating role of general procrastination behaviors to be low in the relationship between self-control and social media addiction. The path analysis has revealed self-control to have a significant and direct effect on social media addiction; persons with low self-control have the tendency to show general procrastination behaviors, while signs of social media addiction have been observed in persons with low self-control and general procrastination behaviors. According to the SEM results, the fit index of the model has been found acceptable; 37% of the total variance in social media addiction levels is explained in the model.
Keywords: Social media addiction; Self-control; General procrastination behaviors; Path analysis; University students; INTERNET USE; FACEBOOK